Role of Physiotherapy in Cardiopulmonary Patients: An Essential Component of Comprehensive Care - Laudari, Shankar; Poudel, Shupriya; Poudel, Shuvechha; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2026)
Cardiopulmonary diseases remain among the leading causes of morbidity, disability, and mortality worldwide, posing a substantial burden on healthcare systems and society. Although advances in medical management, pharmacological therapies, surgical techniques, and interventional procedures have significantly improved survival rates, many patients continue to experience persistent functional limitations, reduced exercise capacity, and impaired quality of life. Consequently, optimal recovery requires a comprehensive multidisciplinary approach in which physiotherapy plays a pivotal role. Cardiopulmonary physiotherapy encompasses evidence-based interventions such as exercise training, respiratory muscle training, airway clearance techniques, breathing exercises, early mobilization, and patient education, all of which contribute to improved exercise tolerance, respiratory mechanics, functional independence, symptom control, and overall health-related quality of life. These interventions also help reduce hospital length of stay, prevent complications, decrease hospital readmissions, and enhance long-term clinical outcomes. This review discusses the current evidence and evolving role of physiotherapy across the spectrum of cardiopulmonary conditions, including heart failure, coronary artery disease, chronic pulmonary diseases, postoperative cardiothoracic surgery, and critical care settings, highlighting its importance in optimizing patient recovery and promoting long-term health and functional well-being.